Evolution of helium triplet transits of close-in gas giants orbiting K dwarfs - Allan, Andrew P. (2024)
Atmospheric escape in exoplanets has traditionally been observed using hydrogen Lyman-α and Hα transmission spectroscopy, but more recent detections have utilized the metastable helium triplet at 1083 nm. Since this feature is accessible from the ground, it offers new possibilities for studying atmospheric escape. Our goal is to understand how the observability of escaping helium evolves during the lifetime of a highly irradiated gas giant. We extend our previous work on 1D self-consistent hydrodynamic escape from hydrogen-only atmospheres as a function of planetary evolution to the first evolution-focused study of escaping hydrogen–helium atmospheres. Additionally, using these novel models we perform helium triplet transmission spectroscopy. We adapt our previous hydrodynamic escape model to now account for both hydrogen and helium heating and cooling processes and simultaneously solve for the population of helium in the triplet state. To account for the planetary evolution, we utilize evolving predictions of planetary radii for a close-in 0.3 MJup gas giant and its received stellar flux in X-ray, hard and soft extreme-ultraviolet (UV), and mid-UV wavelength bins assuming a K-dwarf stellar host. We find that the helium triplet signature diminishes with evolution. Our models suggest that young (≲ 150 Myr), close-in gas giants (∼1 to 2 RJup) should produce helium 1083 nm transit absorptions of ∼ 4 per cent or ∼ 7 per cent, for a slow- or fast-rotating K dwarf, respectively, assuming a 2 per cent helium abundance.